Central and Peripheral Molecular Targets for Anti-Obesity Pharmacotherapy - Valentino, Michael A. (2010)
Obesity has emerged as one of the principle worldwide health concerns of the modern era, and there exists a tremendous unmet clinical need for safe and effective therapies to combat this global pandemic. The prevalence of obesity and its associated co-morbidities, including cardiovascular and metabolic diseases, has focused drug discovery and development on generating effective modalities for the treatment and prevention of obesity. Early efforts in the field of obesity pharmacotherapy centered on agents with indeterminate mechanisms of action producing treatment paradigms characterized by significant off-target effects. During the past two decades, new insights have been made into the physiologic regulation of energy balance and the subordinate central and peripheral circuits coordinating appetite, metabolism, and lipogenesis. These studies have revealed previously unrecognized molecular targets for controlling appetite and managing weight from which has emerged a new wave of targeted pharmacotherapies to prevent and control obesity.